Experimental analysis of pedestrians’ reaction to personal mobility devices : depth camera mounted on PMD approach - L Seng Aung (Nanyang Technological University, 2020)
This project aims to analyze and compare avoiding distance and behaviors of pedestrians with different activities such as walking and running. In this project, experiment was done on Park Connector (PCN) in a natural environment (uncontrolled environment) to prevent Hawthorne effect and to conduct natural reaction of pedestrians. Hawthorne effect takes place when the participants of the study are aware of the experiment, affecting the result of the study. To meet the aim, a program written in C++ Programming language was developed and improved. The purpose of the program is to detect, track and estimate object distance. Distance estimation were calculated based on depth data extracted from RealSense active stereo depth camera D435. Total of 5 experiments were done at Jurong Park Connector (PCN) heading to Lake Side Garden between Corporation Road and Yuan Ching Road near Lake Side MRT Station. 211 people were recorded with different activities such as walking, running, cycling and riding PMD during the experiment. Data analysis was done based on activities, focused mainly on walking and running pedestrians. The results shows that majority of the pedestrians are not aware of the surrounding and did not give way to PMD. Data are presented with graph charts and detailed analysis.